Performance of Procrastinators: On the Value of Deadlines - Fabian Herweg; Daniel Müller (University of Bonn, Bonn Graduate School of Economics (BGSE), 2008)
Earlier work has shown that procrastination can be explained by quasi-hyperbolic discounting. We present a model of effort choice over time that shifts the focus away from completion to performance on a single task. We show that quasi-hyperbolic discounting is detrimental for performance. More intrestingly, we find that being aware of the own self-control problems not necessarily increases performance. Extending this framework to a multi-task model, we show that deadlines help an agent to structure his workload more efficiently, which in turn leads to better performance. Moreover, being restricted by deadlines increases a quasi-hyperbolic discounter's well-being. Thus, we give a theoretical underpinning for recent empirical evidence and numerous casual observations.
Keywords: A12; D11; 330; Effort Choice; Deadlines; (Quasi-) Hyperbolic Discounting; Naiveté; Present-Biased Preferences; Sophistication; Leistungsanreiz; Zeitökonomik; Präferenztheorie; Abzinsung; Theorie